Analisis Strategi Komunikasi Bauran Pemasaran Shopee Peachcosmetics - Kelvin; Aulia, Sisca (Prologia, 2023)
It is used as a practical liaison tool as a communication tool between business people and clients in the realm of online media companies or online trading. Shopee is a mobile application for buying and selling goods online. Several e-commerce sites, particularly Peachcosmetics, have recently benefited from the explosion in popularity and widespread adoption of Shopee accounts. Peachcosmetics uses a Shopee account as one of its marketing sources. Peachcosmetics sells cosmetics that are imported directly from China and sold through PT. JennyCosmetics. In this study, researchers studied the marketing communication strategies used on Peachcosmetics Shopee accounts. In this study the researchers used in-depth interviews, participant observation, and documentation as part of their qualitative case study methodology. The marketing mix is ​​one type of marketing approach that can help in the promotion of Peachcosmetics cosmetic goods. Product, Price, Promotion, Place, People, Physical Evidence, Process, Payment, Packaging. This strategy has been carried out by Peachcosmetics as a strategy to market its products. The strategy is effective, this is evident from the increase in Peachcosmetics sales when. Marketing communication strategies are not only how to market but also how services are provided responsive service for consumers is very important. Penggunaan sosial media dimanfaatkan sebagai alat penghubung praktis sebagai alat komunikasi antara pelaku bisnis dan klien di ranah perusahaan media online atau perdagangan online. Shopee adalah aplikasi seluler untuk membeli dan menjual barang secara online. Beberapa situs e-commerce, khususnya Peachcosmetics, baru-baru ini mendapatkan keuntungan dari ledakan popularitas dan adopsi akun Shopee secara luas. Peachcosmetics menggunakan akun Shopee sebagai salah satu sumber pemasarannya. Peachcosmetics menjual kosmetik yang di import langsung dari China dan di perjualkan melalui melalui PT. JennyCosmetics. Dalam penelitian ini, peneliti mempelajari strategi komunikasi pemasaran yang digunakan pada akun Peachcosmetics Shopee. Dalam studi ini peneliti menggunakan wawancara mendalam, observasi partisipan, dan dokumentasi sebagai bagian dari metodologi studi kasus kualitatif mereka. Bauran pemasaran adalah salah satu jenis pendekatan pemasaran yang dapat membantu dalam promosi barang kosmetik Peachcosmetics. Product, Price, Promotion, Place, People, Physical Evident, Process, Payment, Packaging. Hasil dari penelitian ini menjelaskan 9P dari bauran pemasaran yaitu, Product, Price, Promotion, Place, People, Physical Evident, Process, Payment, Packaging. Hal tersebut dilakukan oleh Peachcosmetics sebagai strategi untuk memasarkan produknya. Strategi komunikasi Peachcosmetics tidak hanya bagaimana cara memasarkan tetapi juga bagaimana pelayanan yang diberikan pelayanan yang responsif bagi konsumen sangat penting.